2018
DOI: 10.1007/s10029-018-1819-8
|View full text |Cite|
|
Sign up to set email alerts
|

Laparoscopic-assisted transversus abdominis plane block as an effective analgesic in total extraperitoneal inguinal hernia repair: a double-blind, randomized controlled trial

Abstract: PurposeLaparoscopic inguinal hernia repair has facilitated early mobilization. Management of post-operative pain is paramount in these day case procedures. The aim of this study was to compare laparoscopic-assisted transversus abdominis plane (TAP) block with periportal local anaesthetic infiltration in managing post-operative pain.MethodsA double-blind, randomized controlled trial was conducted with patients undergoing elective laparoscopic inguinal hernia repair (January 2016–October 2017). The intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 19 publications
3
34
1
Order By: Relevance
“…Recently, we demonstrated that the integration of regional analgesia, notably transversus abdominis plane block, within the context of a standardized approach for postoperative pain management in patients undergoing day case surgeries, has significantly reduced opioid requirements (P<.001) and improved pain control and patient satisfaction (P<.001). 4 Our findings were further substantiated by recent evidence demonstrating the efficacy of transversus abdominis plane block in enhancing postoperative recovery and minimizing opioid requirements in patients undergoing major surgical procedures such as living donor hepatectomy. 5 To date, the adopted prescription opioid control policies for acute pain in patients undergoing surgical procedures are in large part driven by common sense and focus mainly on the duration of use, which is often linked with risks of dependence and unused medication diversion.…”
Section: Crisis In the United Statessupporting
confidence: 72%
See 1 more Smart Citation
“…Recently, we demonstrated that the integration of regional analgesia, notably transversus abdominis plane block, within the context of a standardized approach for postoperative pain management in patients undergoing day case surgeries, has significantly reduced opioid requirements (P<.001) and improved pain control and patient satisfaction (P<.001). 4 Our findings were further substantiated by recent evidence demonstrating the efficacy of transversus abdominis plane block in enhancing postoperative recovery and minimizing opioid requirements in patients undergoing major surgical procedures such as living donor hepatectomy. 5 To date, the adopted prescription opioid control policies for acute pain in patients undergoing surgical procedures are in large part driven by common sense and focus mainly on the duration of use, which is often linked with risks of dependence and unused medication diversion.…”
Section: Crisis In the United Statessupporting
confidence: 72%
“…2,3 Optimal prescribing practices therefore toe the delicate line between providing adequate pain control and minimizing the risk of medication misuse and abuse. 4 This has important implications for the patient and society as a whole.…”
Section: In Replydthe Importance Of Educational Interventions and Regmentioning
confidence: 99%
“…The details of the methodological risk of bias assessment are presented in graphic and summary forms (Figures 2 and 3). In summary, 7 RCTs [10,15,17,20,[22][23][24] had a low risk of bias, and 8 RCTs [11-14, 16, 18, 19, 21] had an unclear risk of bias. The main reasons for the 8 RCTs having an unclear risk of bias were due to a failure to mention the following factors: randomization sequence generation, allocation concealment, blinding of participants and personnel, and blinding of outcome assessment.…”
Section: Risk Of Methodological Bias and The Quality Of Thementioning
confidence: 97%
“…In the subgroup analyses of nonlaparoscopic surgery, compared with WI, TAP block was associated with lower pain scores at rest at 2 h (MD = −0:69, 95% CI (-1.23, -0.16), I 2 = 4%), 6 h (MD = −0:79, 95% CI (-1.22, -0.36), I 2 = 0%), and 24 h (MD = −0:58, 95% CI (-0.90, -0.26), I 2 = 15%) but not at 1 h (MD = −0:32, 95% CI (-1.15, -0.52), I 2 = 64%), and in the subgroup analyses of laparoscopic surgery, compared with WI, TAP block was also associated with lower pain scores at rest at 2 h (MD = −0:94, 95% CI (-1.79, -0.08), I 2 = 2%), 6 h (MD = −0:89, 95% CI (-1.13, -0.65), I 2 = 0%), and 24 h (MD = −0:53, 95% CI (-0.75, -0.31), I 2 = 10%) but not at 1 h (MD = −0:30, 95% CI (-0.63, 0.03), I 2 = 44%) ( Fig S1 to Fig S4). Moreover, in the subgroup analyses of the surgical site in the upper abdomen, compared with WI, TAP block was associated with lower pain scores at rest at 2 h (MD = −0:94, 95% CI (-1.79, -0.08), I 2 = 2%), 12 h (MD = −0:74, 95% CI (-1.28, -0.20), I 2 = 1%), and 24 h (MD = −0:69, 95% CI (-1.00, -0.39), I 2 = 0%) but not 3 [12,17,23], no study reported postoperative pain scores during movement at 12 h, and five studies reported postoperative pain scores during movement at 24 h [14,15,17,23,24]. Compared with WI, TAP block was associated with lower pain scores during movement at 2 h (MD = −1:47, 95% CI (-2.32, 0.62), P = 0:0007), 4 h (MD = −0:65, 95% CI (-1.24, 0.06), P = 0:03), 6 h (MD = −0:73, 95% CI (-1.23, 0.24), P = 0:004), and 24 h (MD = −0:85, 95% CI (-1.16, 0.53), P < 0:00001) but not at 1 h (MD = −1:04, 95% CI (-2.07, 0.00), P = 0:05), and there were low levels of heterogeneity in five analyses (for 1 h: I 2 = 4%; for 2 h: I 2 = 0%; for 4 h: I 2 = 0%; for 6h: I 2 = 0%; and for 24h: I 2 = 0%) ( Figures 10-14).…”
Section: Postoperative Pain Scores Atmentioning
confidence: 99%
See 1 more Smart Citation